IMPACT OF DIGITALIZATION ON THE INNOVATION AND COMPETITIVENESS OF SME’S IN BULGARIA - Filipova, Milena; Yuleva -Chuchulayna, Radostina Emilova (Revista Inclusiones, 2020)
Faced with new dynamic business models and increasing competition in markets, many small and medium-sized enterprises currently face the need for a comprehensive overhaul of previous tactics and strategies. Digitalization plays a key role in this revision. The majority of enterprises in Bulgaria see in digitization a way to optimize the use ofresources, automate production, and improve their interaction with customers and suppliers. Digitalization is a factor that influences the innovation of SME’s. It is important to see it as a list of choices where there are competing requirements that needto be balanced. The main objective of this development is to clarify the nature and specificities of digitalization, to explore the impact of digitalization on innovation and the competitiveness of small and medium-sized enterprises and to propose a modelto increase competitiveness by increasing innovation activity based on digitalization in SME’s. The main research methods used in the development are contingent analysis, method of analysis and synthesis, intuitive and systematic approach.